Morphological Variability of Breadfruit Tree (Artocarpus altilis) in Benin - Assogba, Karl Tamègnon; TCHEKESSI, C. K. Célestin; Bleoussi, Roseline; Sachi, Pivot S.A.; Djogbe, Anayce A.; Banon, Jultesse S.B.; Bokossa Yaou, Innocent; AZOKPOTA, PAULIN (My University, 2019)
The breadfruit tree (Artocarpus altilis), despite its food, therapeutic and agroforestry potential, remained underutilized in Benin due to the lack of information on the species. The objective of this study is to carry out the morphological characterization of the species in order to have a better knowledge of its diversity in Benin, an essential step in its safeguarding and its use. Thus, the discriminatory morphological descriptors in Artocarpus altilis in relation to the agro-ecological diversity of Benin have been identified. Foliar, fruit and seed characteristics were studied. The study areas concerned were the communes of Adjohoun, Avrankou, Dangbo and Adja-Ouèrè spread over the entire geographical range of the breadfruit in Benin. The results obtained showed a significant significance of the variables observed according to the provenances and the descriptors used (the shape of the fruit, the texture of the skin of the fruit, the color of the flesh of the fruit, the number of lobes and the degree of dissection of the fruits. leaves). All fruits sampled did not contain seed. The dendrogram of the 55 populations of Artocarpus altilis studied, resulting from the ascending hierarchical classification, revealed three (3) groups which differ from each other by their morphological characters in the study areas.
Keywords: Morphological; descriptors; fruits; leaves; Artocarpus altilis; Benin